The pathogenesis of pathology of fetal development and its diagnosis (Eurasian Medical Research Periodical, 2023)
The problem of the occurrence of congenital and hereditary pathologies is relevant not only in medical terms. It has a negative impact on the demographic situation in the country and is of great socio-economic significance due to the disability of patients with a severe hereditary disease and the lack of labor in the production of people involved in caring for them. According to scientific research, the share of congenital and hereditary pathology in the structure of morbidity and mortality in newborns and young children in the late XX - early XXI century. is growing steadily: 3-5% of live births are born with congenital malformations, 20-30% of newborns die due to genetic diseases, 30-50% of infant mortality in the postneonatal period is due to congenital malformations. Prognostic risk factors for the pathological development of the fetus are: heredity, consanguinity, complicated obstetric and somatic history, viral infection, inadequate antenatal care, low level of qualification of functionalists, non-compliance with screening terms and examination methods . Methods for early diagnosis of early detection of the studied pathology are given